Analisis Kebijakan Ekspor Pasir Laut Dalam Perspektif Keadilan Ekologi - Nurul Ernawati; I Gusti Ayu Ketut Rachmi Handayani; Rosita Candrakirana (Majelis: Jurnal Hukum Indonesia, 2025)
This research aims to analyze the compatibility of the sea sand export policy, as outlined in Government Regulation No. 26 of 2023 and its implementing regulations in Minister of Trade Regulations No. 20 and 21, with the principles of ecological justice. The research is driven by concerns over the ecological impacts of sea sand exploitation and the potential conflict between economic interests and environmental protection. Using a normative juridical approach and analysis of prevailing laws and regulations, the study finds that the current regulatory framework does not fully reflect the principles of ecological justice. The policy fails to ensure equitable protection for coastal communities and the marine environment. Government Regulation No. 26/2023 does not explicitly mandate Environmental Impact Assessments (AMDAL), does not emphasize conservation as a fundamental principle, and allows room for exploitation in vulnerable coastal and small island areas. Moreover, historical data reveals that similar policies in the past have led to coastal erosion, the loss of outermost islands, and state losses due to illegal practices. Therefore, without proper reassessment and alignment with environmental justice principles, this policy risks exacerbating ecological inequalities.